Organic fertilization in top dressing in jambu production - Taborda Nordi, Nicholas; Ismael Inácio Cardoso, Antonio; Nepomuceno Alves, Thatiane; Pereira de Moraes, Vinícius; Ribeiro de Carvalho, Joseantonio (Comunicata Scientiae, 2022)
In the state of São Paulo, jambu has been grown with a view to its industrial uses. However, there are few works involving mineral nutrition and organic fertilization in jambu, which leads farmers to use fertilizer recommendations intended for other similar leafy crops and several different fertilizers. Thus, the objective of this study is to evaluate different sources of organic fertilizers in top dressing in the production of jambu under organic management. The experiments were carried out at the Experimental Farm of São Manuel, SP, and at the Zodíaco farm, located in the Demétria district, Botucatu, SP. Six treatments (organic fertilizers in top dressing: ferticel®, provaso, castor bean cake, bokashi, hoof and horn powder, and a control without top dressing) were evaluated, using a randomized block design with five replicates. From two harvests in each location, the following characteristics were evaluated: the fresh weight of vegetative parts (FWVP) and of inflorescences (FWI), the total fresh weight (TFW), the number of inflorescences (NI), and the average weight per inflorescence (AWI). The results show an increase of 158% and 78%; 103 and 101%; 143 and 86%; and 144 and 85%, in FWVP, FWI, NI, and TFW, respectively, with the use of hoof and horn powder (the best treatment, not differing from castor bean cake) compared to the control at Zodíaco farm and at the Experimental Farm of São Manuel, respectively. These results indicate that hoof and horn powder and castor bean cake were the best fertilizers in both harvests and locations, with higher production of both fresh and dry weight of the vegetative and reproductive parts of jambu.